Determinants of Investment Behavior of the Younger Generation of Muhammadiyah in Indonesia - Baihaqi Ammy; Andri Soemitra; Zuhrinal M Nawawi (Fundamental and Applied Management Journal, 2026)
This study examines the determinants of investment behavior among the Muhammadiyah Young Generation in Indonesia by integrating Muhammad Abu Zahrah's Maqasid Syariah perspective into the Theory of Planned Behavior (TPB) framework. Data were collected from 300 purposively sampled respondents aged 18–40 years in Medan, Jakarta, Surabaya, Malang, and Yogyakarta between March and April 2026 using a 1–5 Likert scale questionnaire. Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1 was employed to test 15 hypotheses concerning the direct effects of Islamic Financial Literacy (X1), Self-Confidence (X2), Digital Technology (X3), Lifestyle (X4), and Religiosity (X5) on Investment Behavior (Y), as well as moderation by Unstable Income (M1), Risk Tolerance (M2), and Influencer (M3). All 15 hypotheses were supported, with effect sizes (f²) ranging from small to medium: Islamic Financial Literacy emerged as the strongest predictor (β = 0.287; f² = 0.142), reflecting Hifz al-Aql; Lifestyle ranked second (β = 0.241; f² = 0.101), representing tanmiyyah al-mal; followed by Self-Confidence (β = 0.201; f² = 0.073), Religiosity (β = 0.189; f² = 0.061), and Digital Technology (β = 0.163; f² = 0.048). Unstable Income weakened three main effects, Risk Tolerance strengthened three, and influencers produced contextually variable moderation with small effect sizes. The five independent variables and three moderators explained 57.0% of the variance in investment behavior (R² = 0.570; SRMR = 0.062; NFI = 0.924). The primary limitations are the organizational specificity of the sample (restricting generalizability beyond Muhammadiyah populations) and its cross-sectional design. This study contributes an empirically validated Islamic Investment Behavior Model grounded in Abu Zahrah's Maqasid Syariah.